Microscopic identification of the remnant hair or feather of five animal drug components in Shenrongbian pill - Tingguo Kang; Xiahong Feng; Dongmin Yuan; Koji Ohba; Toshihiro Tanaka (Elsevier, 2012)
A comparative study was performed to identify the microscopic characteristics of hair or feather in the five animal drug components contained in Shenrongbian pill. Penis et Testis Canis is 40±0.07 in the medulla index, with long circular, banana or triangular circular shaped medulla cells arranged in one line or network, and the hair cuticle is in imbrication (d, m) and flat wave (p) shape. Penis et Testis Equi is 66±0.10 in the medulla index, with ellipse, spindle or long strip-shaped medulla cells arranged in network, and the hair cuticle is in flat wave shape. Penis et Testis Bovis is 67±0.05 in the medulla index, with rectangle, spindle or polygon-shaped medulla cells arranged in ladder or network form, and the hair cuticle is in flat wave shape. Penis et Testis Mustelae is 29±0.05 in the medulla index, with ellipse-like, square-like or circular shaped medulla cells arranged in one line generally, and the hair cuticle is in acuminate (d, m), imbrication (m,p) and slightly flat wave (p) shape. Musculus et Bonis Passeris is 24±0.05 in the medulla index, with bamboo joint-shaped barbs and unclear medulla cells, without hair cuticle.